Didactic Praxeological Analysis of Indonesian and Singaporean Mathematics Textbooks: Mathematical Practices in Transformation Geometry - Zakiah, Nur Eva; Suryadi, Didi; Suhendra, Suhendra (FKIP Universitas Lampung, 2025)
This study aims to compare the contents of mathematics textbooks from Indonesia and Singapore, focusing on the activities of learning mathematics on transformation geometry material at the junior secondary level. We adopt the concept of didactic praxeology, which is a sub-theory of the Anthropological Theory of The Didactic (ATD). Using the ATD framework, our approach considers textbooks as empirical sources that can reveal knowledge that will be taught in the didactic transposition process. This study uses content analysis techniques with a qualitative approach. Textbooks are analyzed using praxeological analysis; types of tasks and techniques (praxis block) and technology and theory (logos block). The results of the didactic praxeological analysis show that there are differences in mathematical practices between the two textbooks. These differences can be used to complement the activity section in understanding the material. We further discuss our findings to outline the theoretical and methodological aspects of this study, which can potentially contribute to future research on textbooks in mathematics education. Keywords: ATD, praxeology, textbook, transformation geometry.